STRATEGI PENGEMBANGAN PEMBELAJARAN PAI DALAM MENINGKATKAN PRESTASI SISWA DI SMPN1 SAMBENG LAMONGAN - Sirojudin, Didin; Hariyanti, Wiwid Ika (Universitas KH. A. Wahab Hasbullah, 2021)
Strategy is very important to achieve learning objectives so that students can excel and are able to understand and practice the teachings of Islamic Religious Education both at school and at home as well as in the community. The strategy used by this researcher uses qualitative methods. Teachers and principals use a lot of strategies so that students succeed in achieving an achievement. With the teacher's approach, guidance and various extra-curricular activities that make students able to behave like the teachings of Islamic Religious Education. They are accustomed to praying dhuha, there are extras and guidance on reading and memorizing prayers, reading and writing the Qur'an, as well as extra da'wah. They were also taught the value of manners so that their learning outcomes were good and even won a da'wah competition at the district level.Strategy is very important to achieve learning objectives so that students can excel and are able to understand and practice the teachings of Islamic Religious Education both at school and at home as well as in the community. The strategy used by this researcher uses qualitative methods. Teachers and principals use a lot of strategies so that students succeed in achieving an achievement. With the teacher's approach, guidance and various extra-curricular activities that make students able to behave like the teachings of Islamic Religious Education. They are accustomed to praying dhuha, there are extras and guidance on reading and memorizing prayers, reading and writing the Qur'an, as well as extra da'wah. They were also taught the value of manners so that their learning outcomes were good and even won a da'wah competition at the district level.